PALB2 as a factor to predict the prognosis of patients with skull base chordoma - Xiong, Yujia; Li, Mingxuan; Shen, Yutao; Ma, Tianshun; Bai, Jiwei; Zhang, Yazhuo (Frontiers in Oncology, 2022)
Objective This study aimed to study the role of PALB2 on the prognosis of skull base chordoma patients and the proliferation, migration, and invasion of chordoma cells. Methods 187 patients with primary skull base chordoma were involved in the study. Immunohistochemical analysis was used to measure the PALB2 protein expression. Kaplan-Meier analysis, univariate and multivariate Cox analysis were used to evaluate the impact of PALB2 on patient prognosis. A nomogram was established for predicting the progression free survival of chordoma patients. Cell counting kit-8, colony formation, transwell migration, and invasion assays were used to assess the proliferation, migration, and invasion of chordoma cells with PALB2 knockdown. TIMER 2.0 was used to explore the expression and prognostic role of PALB2 in cancers. Results High PALB2 expression indicated an adverse prognosis in chordoma. A nomogram involved PALB2, degree of resection, pathology, and Al-mefty classification could accurately predict the progression free survival of chordoma patients. The proliferation, migration, and invasion of chordoma cells significantly decreased after PALB2 knockdown. Additionally, PALB2 showed high expression in various cancers and was associated with a poor prognosis. Conclusion In summary, our results reveal that high PALB2 expression indicates a poor prognosis of chordoma patients and promotes the malignant phenotypes of chordoma cells in vitro.